Theoretical inhibitor Calculation for Synthesis of Two New thiazole Derivatives - Koparır, Pelin (Niyazi BULUT, 2022)
Abstract: Two newly thiazole (1-(4-(3-methyl-3-phenylcyclobutyl)thiazol-2-yl)-3-(4-nitrophenyl)thiourea and 1-(4-methoxyphenyl)-3-(4-(3-methyl-3-phenylcyclobutyl)thiazol-2-yl)thiourea were synthesise. The molecular formula was characterized using Fourier-Transform Infrared (FT-IR) spectroscopy and Nuclear Magnetic Resonance (NMR). Theoretical vibration was calculated using Gaussian 09W software, and corrosion inhibiting activity was calculated using quantum chemical calculations. Furthermore, the GaussView 5.0 package on the B3LYP/6-311G(d,p) method was used to calculate the energy of the highest occupied molecular orbital (EHOMO), the energy lowest unoccupied molecular orbital (ELUMO)the energy gap (E = ELUMO - EHOMO), the dipole moment (µ), and the percent of transmitted electrons (?N). Based on the results of inhibitor activity, other molecular properties such as hardness (?), softness (?), and electronegativity (?) were calculated. Quantum chemical calculations were used to predict the corrosion inhibiting activities of the derivatives. As a result, the corrosion inhibitor behavior can be predicted without the need for an experimental study. The results show a strong relationship between organic-based corrosion inhibitors and the process's quantum chemical parameters.
Keywords: Chemical Engineering; Kimya Mühendisliği